A sliding selectivity scale for lipid binding to membrane proteins. (August 2016) - Landreh, Michael; Marty, Michael T; Gault, Joseph; Robinson, Carol V
Highlights: The interactions between membrane proteins and lipids are heterogenic. Annular lipids act as solvent but may also form functionally important contacts. Mass spectrometry and MD simulations capture a broad range of lipid interactions. Annular lipid binding exhibits different degrees of selectivity. This sliding scale of selectivity suggests functional roles for lipid subsets. Abstract : Biological membranes form barriers that are essential for cellular integrity and compartmentalisation. Proteins in the membrane have co-evolved with their hydrophobic lipid environment, which serves as a solvent for proteins with very diverse requirements. As a result, their interactions range from non-selective to highly discriminating. Mass spectrometry enables us to monitor how lipids interact with membrane proteins and assess their effects on structure and dynamics. Recent studies illustrate the ability to differentiate specific lipid binding, preferential interactions with lipid subsets, and nonselective annular contacts. Here, we consider the biological implications of different lipid-binding scenarios and propose that binding occurs on a sliding selectivity scale, in line with the view of biological membranes as facilitators of dynamic protein and lipid organization.